2018
DOI: 10.1007/s10973-018-7119-9
|View full text |Cite
|
Sign up to set email alerts
|

Titanium dioxide doped with vanadium as effective catalyst for selective oxidation of diphenyl sulfide to diphenyl sulfonate

Abstract: Diphenyl sulfide was oxidized to sulfoxide and sulfone over V-doped TiO 2 using a 30% solution of H 2 O 2 . The TiO 2 samples with different intended content of vanadium (0.02, 0.05, 0.1 and 0.18 mass%) were prepared by incipient wetness impregnation. Physicochemical properties of the V-doped TiO 2 were characterized by chemical analysis (ICP-OES), X-ray diffraction (XRD/in situ HT-XRD), UV-Vis diffuse reflectance spectrometry (UV-Vis DRS), N 2 -sorption measurements, electron paramagnetic resonance and cyclic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 36 publications
(51 reference statements)
1
12
0
Order By: Relevance
“…A similar effect was reported and discussed in our previous paper for TiO 2 doped with vanadium. 22 The phase composition of the samples was analysed using Xray diffraction and Raman spectroscopy. The results of these analyses are presented in Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A similar effect was reported and discussed in our previous paper for TiO 2 doped with vanadium. 22 The phase composition of the samples was analysed using Xray diffraction and Raman spectroscopy. The results of these analyses are presented in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…A similar effect of the anatase to rutile transformation in the presence of small amounts of vanadium was recently reported by Shao et al, 25 as well as in our previous paper. 22 This phenomenon could be explained by the possible incorporation of V 4+ cations into the vacant Ti 4+ positions in anatase. 26,27 Such a substitution is possible due to the similar ionic radii of Ti 4+ (0.061 nm) and V 4+ (0.058 nm).…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, TiO 2 doped with vanadium was found to be an active catalyst of Ph 2 S oxidation giving nearly 100% conversion of Ph 2 S with high selectivity to Ph 2 SO 2 . 15 SiO 2 –TiO 2 mesoporous xerogel catalyses oxidation to the final product, diphenyl sulfone, with the selectivity of 85%. 16 Furthermore, it was confirmed that titanosilicate zeolites ( inter alia , Ti-beta, 17 Ti-MWW, 18 Ti-FER, MTS-1 (ref.…”
Section: Introductionmentioning
confidence: 99%
“…Now, the ODS method is an interesting topic for researchers to introduce an economic and efficient method for desulfurization of fuels . Various catalysts are previously used in the ODS reaction such as W, Mo, V, Ti, and Fe Oxides . Among them, the catalysts based on molybdenum oxide has shown good results in ODS reaction .…”
Section: Introductionmentioning
confidence: 99%
“…[7][8][9][10][11][12][13] Various catalysts are previously used in the ODS reaction such as W, Mo, V, Ti, and Fe Oxides. [14][15][16] Among them, the catalysts based on molybdenum oxide has shown good results in ODS reaction. [17][18][19][20] Furthermore, alumina, activated carbon, and silica are commonly used as the ODS catalyst supports.…”
Section: Introductionmentioning
confidence: 99%